Laminate magnet

The laminated magnet design, with a curved rare earth magnet structure and an inorganic crystal insulating layer, addresses the challenges of eddy current losses and magnetic flux concentration, achieving enhanced performance in magnetic flux density and orientation.

JP2025039997APending Publication Date: 2025-03-24NITERRA CO LTD +2

Patent Information

Application Number
JP2023146626
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-09-11
Publication Date
2025-03-24

AI Technical Summary

Technical Problem

Existing laminated magnets face challenges in reducing eddy current losses and effectively concentrating magnetic flux.

Method used

A laminated magnet design featuring a plurality of rare earth magnets with a curved shape convex in one direction, laminated with an insulating layer primarily composed of inorganic crystals, which enhances the average orientation of the magnet's outer periphery and reduces eddy current losses.

Benefits of technology

The proposed laminated magnet design significantly reduces eddy current losses and concentrates magnetic flux, achieving high average orientation and improved magnetic flux density distribution.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025039997000001_ABST
    Figure 2025039997000001_ABST
Patent Text Reader

Abstract

To provide a new noble laminate magnet that can reduce eddy current loss generated inside and can concentrate magnetic flux.SOLUTION: A laminate magnet 10 is formed of multiple magnets 11 and insulating layers 13 stacked in a first direction. The magnet 11 contains rare earth elements. The magnet 11 are curved that is convex in a second direction when viewed from the first direction, and the average orientation degree of each 1 mm-wide unit centered on the normal at multiple points from one end on the convex side of the curve in the second direction of the outer circumference of the magnet 11 when viewed from the first direction is 90% or more. The insulating layer 13 is mainly composed of inorganic crystals.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to laminated magnets. [Background technology]

[0002] Patent Document 1 discloses a rare earth magnet having a resistive layer formed on the surface of a magnet body. It also shows a laminated magnet in which a plurality of rare earth magnets are stacked and molded with resin for use. Furthermore, various magnets have been proposed for the purpose of reducing eddy current loss (eg, Patent Documents 2-4). [Prior art documents] [Patent documents]

[0003] [Patent Document 1] JP 2017-174962 A [Patent Document 2] JP 2013-219911 A [Patent Document 3] JP 2007-157903 A [Patent Document 4] JP 2003-164083 A Summary of the Invention [Problem to be solved by the invention]

[0004] In recent years, there have been various demands for laminated magnets. For example, there is a demand for new laminated magnets that can reduce eddy current loss generated inside and can concentrate magnetic flux. The present disclosure has been made in consideration of the above-mentioned circumstances, and has an object to provide a novel laminated magnet that can reduce eddy current loss generated inside and can concentrate magnetic flux. The present disclosure can be realized in the following forms. [Means for solving the problem]

[0005] [1] A laminated magnet in which a plurality of magnets and insulating layers are laminated in a first direction, the magnet contains a rare earth element and has a curved shape that is convex in a second direction when viewed from the first direction, The average orientation degree of each portion of a 1 mm width centered on a normal line at a plurality of points from one end to the other end on the outer periphery of the magnet as viewed from the first direction is 90% or more, The insulating layer is a laminated magnet mainly composed of inorganic crystals. Effect of the Invention

[0006] According to the present disclosure, it is possible to provide a novel laminated magnet that can reduce eddy current loss generated inside and concentrate magnetic flux. [Brief description of the drawings]

[0007] [Figure 1] FIG. 2 is a perspective view showing a schematic example of a laminated magnet. [Diagram 2] FIG. 2 is a top view of a laminated magnet. [Diagram 3] 3 is a cross-sectional view taken along line AA in FIG. 2. [Figure 4] FIG. 1 is a cross-sectional view of another example 1 of a laminated magnet. [Diagram 5] FIG. 5 is an enlarged view showing a part of FIG. 4. [Figure 6] FIG. 2 is a diagram for explaining a method for measuring the average orientation degree of magnets. [Figure 7] FIG. 11 is a diagram for explaining a method for measuring the average degree of orientation of magnets in Other Example 2. [Figure 8] FIG. 2 is a diagram illustrating each part for measuring an average degree of orientation. [Figure 9] FIG. 2 is a cross-sectional view illustrating a schematic view of a part of a motor. [Figure 10] FIG. [Figure 11] 13 is a diagram showing a simulation result of sample A and an image of the distribution of magnetic flux density. [Figure 12] 13 is a diagram showing a simulation result of sample B and an image of the distribution of magnetic flux density. [Figure 13]13 is a diagram showing a simulation result of sample C and an image of the distribution of magnetic flux density. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0008] The present disclosure will be described in detail below. In this specification, a description using "-" for a numerical range includes both the lower limit and the upper limit unless otherwise specified. For example, the description "10-20" includes both the lower limit "10" and the upper limit "20". In other words, "10-20" has the same meaning as "10 or more and 20 or less". In this specification, the upper limit and the lower limit of each numerical range can be arbitrarily combined. Hereinafter, the Z-axis direction in each figure is the stacking direction (first direction) of the laminated magnet 10. One direction perpendicular to the Z-axis direction is the X-axis direction (also referred to as the second direction), and the direction perpendicular to the Z-axis direction and the X-axis direction is the Y-axis direction.

[0009] 1.Laminated magnet 10 As illustrated in Figures 1 to 3, the magnet stack 10 is formed by stacking a plurality of magnets 11 and insulating layers 13 in a first direction. The magnets 11 contain a rare earth element. When viewed from the first direction, the magnets 11 have a curved shape that is convex in a second direction, and the average orientation degree of each portion of a 1 mm width centered on a normal line at multiple points from one end to the other end on the curve on the convex side in the second direction on the outer periphery of the magnet 11 when viewed from the first direction is 90% or more. The insulating layer 13 is mainly composed of inorganic crystals.

[0010] (1) Magnet 11 Magnet 11 is a permanent magnet containing a rare earth element. From the viewpoint of having good magnetic properties, magnet 11 is preferably a rare earth sintered magnet. The total amount of rare earth elements can be adjusted by changing the content of rare earth elements in the raw materials of magnet 11 and insulating layer 13.

[0011] The composition of magnet 11 is not particularly limited as long as it contains rare earth elements. From the viewpoint of increasing the magnetic flux density, the total amount of rare earth elements in magnet 11 is preferably 31.0 mass% or less, and more preferably 29.5 mass% or less. The lower limit of the total amount of rare earth elements in magnet 11 is, for example, 27 mass% or more, and may be 28 mass% or more, or 28.5 mass% or more. The total amount of rare earth elements in magnet 11 can be measured by X-ray fluorescence analysis.

[0012] The magnet 11 may be, for example, a magnet containing a rare earth element (R), a transition metal element (T), and boron (B). Such a magnet is also called an RTB magnet.

[0013] The rare earth element may be, for example, one or more selected from the group consisting of neodymium (Nd), praseodymium (Pr), terbium (Tb), dysprosium (Dy), samarium (Sm), yttrium (Y), scandium (Sc), lanthanum (La), cerium (Ce), europium (Eu), gadolinium (Gd), holmium (Ho), ytterbium (Yb), and lutetium (Lu). Among these, it is preferable that the rare earth element contains one or more of Nd, Pr, Dy, and Tb, and it is more preferable that Nd is contained as the main component. Incidentally, the term "mainly Nd" means that the content (mass%) of Nd is the highest among the rare earth elements. The B content of magnet 11 is preferably 0.1% by mass or more and 3% by mass or less, and more preferably 0.5% by mass or more and 1.5% by mass or less.

[0014] The transition metal element may be, for example, one or more selected from the group consisting of iron (Fe), cobalt (Co), and nickel (Ni). Among these, from the viewpoint of magnetic properties, it is preferable that the transition metal element contains one or more of Fe and Co, and it is more preferable that the transition metal element contains Fe as the main component. Incidentally, "containing Fe as the main component" means that the content (mass%) of Fe is the highest among the transition metal elements. The transition metal element content is preferably 60% by mass or more, and more preferably 65% ​​by mass or more, of the entire magnet 11. There is no particular upper limit to the transition metal element content, and it can be, for example, 73% by mass or less of the entire magnet 11. Furthermore, when Fe and Co are contained, part of the Fe may be substituted with Co. For example, when the total of Fe and Co is 100% by mass, the Co content can be greater than 0% by mass and 1% by mass or less.

[0015] Magnet 11 may contain elements other than the above elements (hereinafter also referred to as other elements). The other elements include one or more elements selected from the group consisting of aluminum (Al), copper (Cu), zinc (Zn), indium (In), silicon (Si), phosphorus (P), sulfur (S), titanium (Ti), vanadium (V), chromium (Cr), manganese (Mn), nickel (Ni), gallium (Ga), germanium (Ge), zirconium (Zr), niobium (Nb), molybdenum (Mo), palladium (Pd), silver (Ag), cadmium (Cd), tin (Sn), antimony (Sb), hafnium (Hf), tantalum (Ta), and tungsten (W). The content of other elements is preferably 0% by mass or more and 3% by mass or less of the entire magnet 11.

[0016] From the viewpoint of improving the coercive force, it is more preferable that the magnet 11 has a region in which the concentration of the heavy rare earth element decreases from at least a part of the surface of the magnet 11 toward the inside of the magnet 11. In FIG. 5, the decrease in the concentration of the heavy rare earth element is represented by the shade of the hatching. Parts with a high concentration of the heavy rare earth element are shown with a dark shade, while parts with a low concentration are shown with a light shade. A configuration having a region in which the concentration of the heavy rare earth element decreases can contribute to reducing the amount of the heavy rare earth element added while maintaining magnetic properties. The heavy rare earth element may be one or more selected from the group consisting of terbium (Tb), dysprosium (Dy), gadolinium (Gd), holmium (Ho), europium (Eu), thulium (Tm), ytterbium (Yb), and lutetium (Lu). Among these, the heavy rare earth element is preferably one or more of Dy and Tb. The region in magnet 11 where the concentration of the heavy rare earth element is reduced can be formed, for example, by applying a material containing the heavy rare earth element to the surface of magnet 11 and then heat treating it. Details will be described later.

[0017] The magnet 11 is, for example, NdFe 14 It is preferable that the magnet 11 has a main phase of NdFe and a rare earth rich phase having a higher rare earth element content than the main phase. The magnet 11 may further have a boron rich phase having a higher boron content than the main phase. The main phase usually has a tetragonal crystal structure. For example, the above-mentioned NdFe 14 B has a tetragonal crystal structure. The main phase of magnet 11 can be identified as the component with the greatest peak intensity by subjecting magnet 11 to XRD (X-ray diffraction) analysis. 14 When the peak intensity of B is the largest, magnet 11 is NdFe 14 It can be determined that the main phase is B.

[0018] The average degree of orientation of magnets 11 and a method for measuring it will be described later. In Figures 2 and 3, the outline arrows indicate the orientation direction. Multiple magnets 11 can be used, for example, lined up in a direction perpendicular to the orientation direction, as shown in Figure 3.

[0019] The shape of the magnet 11 is not particularly limited. For example, the magnet 11 is preferably plate-shaped. The plate-shaped magnet 11 has a smaller distance from the surface to the deepest part than a block-shaped magnet having a larger thickness. Therefore, the plate-shaped magnet 11 is suitable because it is easy to diffuse the heavy rare earth element to the inside when the heavy rare earth element is diffused through grain boundaries. The plate-shaped magnet 11 can be suitably used as a laminated magnet in which multiple magnets 11 and insulating layers 13 are laminated. In the laminated magnet 10 of FIG. 1, multiple magnets 11 are laminated with the thickness direction of the plate-shaped magnet 11 as the lamination direction. In this laminated magnet 10, the magnets 11 and the insulating layers 13 are laminated alternately. In the laminated magnet, each magnet 11 may also be referred to as a magnet body. The shape of the magnet 11 when viewed from the first direction (Z-axis direction) will be described later.

[0020] The thickness of the magnet 11 is preferably 0.5 mm or more and 4.0 mm or less, and more preferably 1.2 mm or more and 2.5 mm or less. If the thickness of the magnet 11 is 0.5 mm or more, the magnet 11 can be easily formed while ensuring an average degree of orientation. If the thickness of the magnet 11 is 4.0 mm or less, the heavy rare earth element can be easily diffused to the inside. Furthermore, if the thickness is 4.0 mm or less, the eddy current loss inside the laminated magnet 10 can be suitably reduced. The dimensions of the plate-shaped magnet 11 in the direction perpendicular to the thickness are not particularly limited. For example, the magnet 11 can be 0.5 mm or more and 4.0 mm or less in thickness, 4 mm or more and 10 mm or less in length, and 10 mm or more and 30 mm or less in width.

[0021] (2) Insulating layer 13 The insulating layer 13 is mainly composed of inorganic crystals. The inorganic crystals are preferably non-magnetic crystalline particles. Incidentally, "mainly composed of inorganic crystals" means that the content of inorganic crystals in the insulating layer 13 is 50% by mass or more. Incidentally, the content of inorganic crystals in the insulating layer 13 is preferably 80% by mass or more, more preferably 90% by mass or more, and may be 100% by mass. The composition of insulating layer 13 can be analyzed by the following method: The presence of inorganic crystals is determined by micro X-ray analysis or XRD analysis, and the content of inorganic crystals is calculated in combination with composition analysis by EPMA (Electron Probe Micro Analyser).

[0022] From the viewpoint of reducing eddy current loss, it is preferable that the insulating layer 13 contains one or more inorganic crystals selected from the group consisting of CaF2, BaF2, SrF2, MgF2, Al2O3, ZrO2, Dy2O3, Tb2O3, Nd2O3, TbF3, DyF3, LiF, SiO2, BN, ZrB2, Si3N4, TiB2, Pr2O3, and SiC. From the viewpoint of reducing eddy current loss, the insulating layer 13 preferably contains at least a fluoride of Group 2A of the periodic table as an inorganic crystal. More preferably, the insulating layer 13 contains at least one or more fluorides of Group 2A of the periodic table selected from the group consisting of CaF2, BaF2, SrF2, and MgF2 as the fluoride of Group 2A of the periodic table. Of these, the insulating layer 13 particularly preferably contains CaF2.

[0023] When the entire inorganic crystal is taken as 100 mass %, the insulating layer 13 preferably contains 80 mass % or more of a fluoride of Group 2A of the periodic table as an inorganic crystal, more preferably 90 mass % or more, and even more preferably 95 mass % or more. The upper limit of the content of the fluoride of Group 2A of the periodic table is not particularly limited, and may be, for example, 100 mass %.

[0024] When insulating layer 13 is mainly composed of Group 2A fluoride of the periodic table, the raw material for insulating layer 13 preferably contains the above-mentioned compound of a heavy rare earth element in addition to the Group 2A fluoride of the periodic table. If the raw material for insulating layer 13 contains the above-mentioned compound of a heavy rare earth element, the heavy rare earth element can be favorably diffused into magnet 11. The heavy rare earth element contained in the raw material for insulating layer 13 diffuses into magnet 11 after heat treatment. For this reason, insulating layer 13 of the obtained magnet laminate 10 contains almost no heavy rare earth element. There is no particular limitation on the mass ratio between the fluoride of Group 2A of the periodic table and the compound of a heavy rare earth element in the raw material of the insulating layer 13. The mass ratio between the fluoride of Group 2A of the periodic table and the compound of a heavy rare earth element in the raw material of the insulating layer 13 can be, for example, 20:80 to 40:60.

[0025] It is sufficient that the insulating layer 13 is present at least between the magnets 11, 11. The insulating layer 13 is arranged, for example, as follows. The insulating layer 13 may be arranged so as to cover the entire surface of the magnet 11 (see FIG. 4). In the example of FIG. 4, both upper and lower main surfaces 11A and both side surfaces 11B of each magnet 11 are covered with the insulating layer 13, and the insulating layer 13 is arranged so as to cover the entire surface of the magnet 11. The insulating layer 13 may be arranged in a form covering a part of the surface of the magnet 11 (see FIG. 3). In the example of FIG. 3, the side surface 11B of each of the magnets 11 is not covered with the insulating layer 13, and the insulating layer 13 is arranged in a form covering a part of the surface of the magnet 11. In the example of FIG. 3, the main surface 11A of the uppermost magnet 11 is covered with the insulating layer 13 on one side (lower side), but is not covered with the insulating layer 13 on the other side (upper side), and the insulating layer 13 is arranged in a form covering a part of the surface of the magnet 11. Similarly, in the example of FIG. 3, the main surface 11A of the lowermost magnet 11 is covered with the insulating layer 13 on one side (upper side), but is not covered with the insulating layer 13 on the other side (lower side), and the insulating layer 13 is arranged in a form covering a part of the surface of the magnet 11.

[0026] The insulating layer 13 is preferably provided so as to be in direct contact with the magnet 11. The insulating layer 13 may also be an insulating bonding layer that bonds (adheres) the magnets 11, 11 located on both sides. From the viewpoint of bonding the magnets 11, 11 with sufficient strength, the insulating layer 13 preferably has an area in which components derived from the insulating layer 13 and components derived from the magnet 11 are mixed in the arrangement direction (Z-axis direction) of the multiple magnets 11. Such a laminated magnet 10 can be suitably formed by hot pressing. The conditions for hot pressing will be described later.

[0027] The insulating layer 13 may be provided along the orientation direction of the magnetic field of each magnet 11 (e.g., the X-axis direction in FIG. 3, the direction of the white arrow in FIG. 3), or along a direction intersecting the orientation direction (e.g., the X-axis direction in FIG. 3) (e.g., the Z-axis direction in FIG. 3). As shown in FIG. 9, when the magnet stack 10 is used as a motor magnet or the like, the insulating layer 13 is preferably provided along the orientation direction of the magnets 11 (the X-axis direction in FIG. 9) from the viewpoint of efficiently reducing eddy current loss. With this configuration, the insulating layer 13 is disposed approximately parallel to the direction in which the magnetic flux generated in the stator 31 passes through the magnet stack 10 (the X-axis direction in FIG. 9), so that eddy current loss can be effectively reduced.

[0028] The thickness T of the insulating layer 13 is not particularly limited. From the viewpoint of ensuring sufficient insulation, the thickness T of the insulating layer 13 is preferably 5 μm or more, more preferably 9 μm or more, and even more preferably 12 μm or more. From the viewpoint of ensuring magnetic properties, the thickness T of the insulating layer 13 is preferably 30 μm or less, more preferably 25 μm or less, and even more preferably 18 μm or less. From these viewpoints, the thickness T of the insulating layer 13 is preferably 5 μm or more and 30 μm or less, more preferably 9 μm or more and 25 μm or less, and even more preferably 12 μm or more and 18 μm or less. The thickness T of the insulating layer 13 is measured, for example, by observing the cross section of the magnet laminate 10 with a SEM (scanning electron microscope) and determining the distance between the magnets 11 located on both sides of the insulating layer 13 (see FIG. 5).

[0029] (3) Configuration of magnet stack 10 From the viewpoint of reducing eddy current loss, it is preferable that 10 or more magnets 11 are used per 50 mm dimension of the magnet stack 10 in the first direction, preferably 20 or more magnets are used, and preferably 25 or more magnets are used. There is no particular upper limit on the number of magnets, and it may be, for example, 35 or less.

[0030] (4) Shape of magnet 11 as viewed from a first direction Magnet 11 has a curved shape that is convex in a second direction when viewed from a first direction. In this embodiment, the first direction corresponds to the Z-axis direction. The second direction corresponds to the X-axis direction.

[0031] The shape of the magnet 11 is not particularly limited as long as it is a curved shape that is convex in the second direction. From the viewpoint of concentrating magnetic flux, the magnet 11 is preferably an arc shape. In the present disclosure, the shape of the outer periphery of the magnet when viewed from the first direction, in which the curve C1 on the convex side is substantially arc-shaped, and the line opposing the curve C1 (opposing line C2 described later) is also substantially arc-shaped, is referred to as an arc shape. That is, the arc shape includes two substantially arc-shaped curves that extend parallel to each other in the contour line of the outer periphery of the magnet when viewed from the first direction. The magnet 11 may be a convex curved shape other than an arc shape.

[0032] Below, magnet 11 in Figures 6 and 7 will be specifically explained, with the curve on the convex side of the outer periphery of magnet 11 when viewed from the Z-axis direction being curve C1, and the line tracing the side opposite curve C1 being opposite line C2. Magnet 11 in Figure 6 is an arc-shaped magnet. Curve C1 is an arc of a perfect circle. The radius of curvature of curve C1 is constant. Counterline line C2 is an arc of a perfect circle that is concentric with curve C1. In Figure 6, the center of curvature of curve C1 and counterline line C2 is indicated by point O. Counterline line C2 is a curve (a parallel curve to curve C1) that is a constant distance from each point on curve C1 in the normal direction. The magnet 11 in FIG. 7 is an example of a convex curved shape other than a circular arc shape. This magnet 11 is approximately U-shaped. The curve C1 is a curve with a changing radius of curvature. Specifically, the curve C1 has a straight portion and a portion that is bent from the straight portion. When the radius of curvature of the curve C1 changes, it is preferable that the radius of curvature changes continuously. The counter line C2 is a curve (a parallel curve to the curve C1) that is at a certain distance from each point on the curve C1 in the normal direction.

[0033] The radius of curvature of the curve C1 is not particularly limited. Hereinafter, the smallest radius of curvature among the radii of curvature of the points on the curve C1 will be referred to as the minimum radius of curvature. If the curve C1 is an arc of a perfect circle, the minimum radius of curvature is the same as the radius of the perfect circle. The minimum radius of curvature of the curve C1 is preferably 10 mm or more, more preferably 20 mm or more, and even more preferably 30 mm or more. From the viewpoint of favorably concentrating the magnetic flux density, the minimum radius of curvature of the curve C1 is preferably 100 mm or less, more preferably 75 mm or less, and even more preferably 50 mm or less. From these viewpoints, the minimum radius of curvature of the curve C1 is preferably 10 mm or more and 100 mm or less, more preferably 20 mm or more and 75 mm or less, and even more preferably 30 mm or more and 50 mm or less. When the curve C1 is an arc of a perfect circle, the central angle of the curve C1 is preferably 120° or more and 180° or less, and more preferably 150° or less.

[0034] (5) Average orientation of magnet 11 Magnet 11 has an average degree of orientation of 90% or more in each of 1 mm-wide portions 12 centered on normal Nn at multiple points Pn from one end to the other end on curve C1 on the convex side in the second direction on the outer periphery of magnet 11 when viewed from the first direction. The average degree of orientation can be, for example, 92% or more, 94% or more, 95% or more, or 96% or more. The higher the average degree of orientation of magnet 11, the better, but it is usually 99.5% or less.

[0035] A method for measuring the average degree of orientation in magnet 11 will now be described with reference to FIGS. The average orientation of magnet 11 is determined as the average orientation of each portion of 1 mm width centered on normal Nn at multiple points Pn from one end to the other end on curve C1 on the convex side of the outer periphery of magnet 11 as viewed from the first direction (Z-axis direction). The number of multiple points Pn is not particularly limited. When the size of magnet 11 is sufficiently small, the number of multiple points Pn may be two, but is preferably five or more. The number of multiple points Pn is usually 10 or less.

[0036] First, a number of points Pn are identified as shown in FIG. 6. In this embodiment, five points P1-P5 are identified. In the magnet 11, points P1 and P5 at both ends are taken at a position within 5 mm from one end (e.g., the left end) of the curve C1 on the convex side, and a position within 5 mm from the other end (e.g., the right end). A number of points (points P2-P4 in this embodiment) are taken in order from one end at positions that divide the distance between points P1 and P5 at both ends of the curve C1 at equal intervals (positions that divide the distance into four in this embodiment). Note that point P3 in this embodiment is located in the middle of the curve C1.

[0037] In the curve C1, a normal line N1-N5 at each of the points P1-P5 is identified. A portion 12 having a width of 1 mm centered on the normal line Nn is cut out from the magnet 11. Each portion 12 is, for example, in the shape of a substantially rectangular prism, as shown in FIG. 8. In reality, the top and bottom surfaces in FIG. 8 are curved surfaces. The degree of orientation of each portion 12 is measured, for example, by a pulse-type high magnetic field measuring device (magnetic field: 4T). If the cut-out portion does not fit into the measuring device, a sample of a size that can fit into the measuring device is cut out from the center of the cut-out portion. The average value of the degrees of orientation of each portion 12 is calculated as the average degree of orientation. For magnet 11 in FIG. 7, the average degree of orientation can be calculated using the same measurement method as above.

[0038] It should be noted that magnet 11 can achieve the above average degree of orientation of 90% or more by applying a magnetic field that spreads in the normal direction of curve C1 of magnet 11 in the orientation step described below, for example.

[0039] 2. Manufacturing method of laminated magnet 10 There is no particular limitation on the method for manufacturing the magnet laminate 10. An example of a method for manufacturing the magnet laminate 10 in which the magnets 11 and the insulating layers 13 are alternately stacked will be described below.

[0040] (1) SC alloy preparation process A raw alloy (strip cast alloy (SC alloy)) containing rare earth elements, transition metal elements, boron, and the like is prepared.

[0041] (2) Hydro-crushing process In a hydrogen atmosphere, the SC alloy is allowed to absorb hydrogen at a specified temperature (e.g., 200 degrees) for a specified time (e.g., 1 hour to 5 hours), thereby embrittling the grain boundaries (rare earth rich phase) of the SC alloy.

[0042] (3) Coarse grinding process, first lubricant addition process The SC alloy powder that has been subjected to the hydrogen crushing process is coarsely crushed (coarse crushing process). At this time, a lubricant may be added to the SC alloy powder (first lubricant addition process). This process may be performed, for example, in an inert atmosphere (nitrogen atmosphere, argon atmosphere, etc.).

[0043] (4) Fine grinding process, second lubricant addition process The SC alloy powder after the coarse pulverization step is pulverized to a predetermined average particle size D50 (fine pulverization step). The average particle size D50 can be, for example, 2.0 μm-3.5 μm. At this time, in order to improve the fluidity of the pulverized powder, a lubricant may be added to the finely pulverized SC alloy powder (second lubricant addition step). This step is preferably carried out, for example, in an inert atmosphere (nitrogen atmosphere, argon atmosphere, etc.).

[0044] (5) Powder filling process, orientation process, molding process The powder of the SC alloy after the pulverization process is filled into a mold. This process may be performed, for example, under an inert atmosphere (nitrogen atmosphere, argon atmosphere, etc.). The mold has a plurality of molding spaces of a predetermined thickness. Each molding space is partitioned, for example, by a plurality of partition plates. A magnetic field is applied in a predetermined direction to the mold after the powder is filled to align the orientation of the SC alloy powder. For example, when the magnet 11 has an arc shape as shown in FIG. 6, a radial magnetic field (a magnetic field in which magnetic lines spread radially) is applied. Thereafter, the powder of the SC alloy filled into the mold is pressed to form a molded body of the SC alloy. In this way, a molded body of the SC alloy having a predetermined degree of orientation (for example, an average degree of orientation of 90% or more) and a predetermined thickness (for example, a thickness of 1.2 mm or more and 2.5 mm or less) can be obtained without a cutting process. The shape of the molded body can be made into a desired shape by changing the shape of the mold into which the powder of the SC alloy after the pulverization process is filled. Furthermore, by using an orientation coil that matches the shape of the molded body, the average degree of orientation of the molded body can be increased.

[0045] (6) Mold removal process, first firing process The molded body is removed from the mold (mold removal step). The molded body is fired at a predetermined firing temperature (e.g., 900°C-1200°C) for a predetermined time (e.g., 2 hours-5 hours) (first firing step). This firing is preferably performed in a vacuum. Prior to this firing, heating at a temperature lower than the firing temperature may be performed for dehydrogenation.

[0046] (7) Insulation layer coating process The raw material of the insulating layer 13 is applied to the surface of the fired compact. The raw material of the insulating layer 13 may be, for example, a mixture of raw material powder of an inorganic crystal component, a compound powder containing a heavy rare earth element, and a solvent. The raw material of the insulating layer 13 may be applied to at least one main surface of the compact, or may be applied to both main surfaces. The main surface of the compact is the surface corresponding to the main surface 11A of the magnet 11. The raw material of the insulating layer 13 may be applied to the entire surface of the compact, that is, to both main surfaces and side surfaces when the compact is in the form of a plate.

[0047] (8) Laminate temporary fixing process A predetermined number of molded bodies coated with an insulating layer are stacked and temporarily fixed. Hereinafter, the temporarily fixed stack of molded bodies is also referred to as a laminate. According to this method, it is possible to manufacture plate-shaped magnets 11 without the need for a cutting process or the like to cut out plate-shaped magnets from a larger magnet.

[0048] (9) Hot pressing process The temporarily fixed laminate is placed in a hot press mold and hot pressed with uniaxial pressure. This process is carried out, for example, in a vacuum atmosphere (for example, 10 -3 Pa-10 -4 The hot pressing may be performed at a pressure of 1000 MPa (1 Pa) or in an inert atmosphere (such as a nitrogen atmosphere or an argon atmosphere). The hot pressing temperature may be, for example, 700°C to 1100°C. The hot pressing pressure time may be, for example, 1 second to 1 hour. The hot pressing pressure is preferably 3 MPa or more, more preferably 5 MPa or more, and further preferably 8 MPa or more. The upper limit of the hot pressing pressure is not particularly limited, and is, for example, 100 MPa or less. The heat treatment time of the hot pressing may be, for example, 10 minutes to 20 hours. Through the above series of steps, a magnet stack 10 including magnets 11 and insulating layers 13 is manufactured. The magnet stack 10 is formed by bonding a plurality of magnets 11 together via insulating layers 13, forming an integrated unit.

[0049] The hot pressing process allows the heavy rare earth elements (Tb, Dy, etc.) contained in the raw material of the applied insulating layer 13 to diffuse into the magnet 11. The hot pressing process also allows the magnet 11 (e.g., NdFe 14 The rare earth components (Nd components) in B) flow out to the surface of magnet 11, forming a surface layer of a rare earth-rich phase (Nd-rich phase) near the interface with insulating layer 13 (e.g., a layer containing CaF2) in magnet 11. Furthermore, this hot pressing process allows insulating layer 13 to be made sufficiently thin, and the thickness of insulating layer 13 can be made uniform.

[0050] The laminated magnet 10 obtained in the above manner can be regarded as a laminated magnet manufactured by hot pressing (hot uniaxial pressing) a laminate having the raw material of the insulating layer 13 sandwiched between at least a pair of magnets 11, 11 (sintered bodies of SC alloy) so that pressure is applied in a direction that crushes the raw material of the insulating layer 13. Furthermore, the laminated magnet 10 can be understood as a laminated magnet manufactured by arranging a first magnet 11 (sintered body of SC alloy), the raw material of the insulating layer 13, and a second magnet 11 (sintered body of SC alloy) in this order to form a laminate, and then heating the laminate while applying pressure to both sides of the first magnet 11 and the second magnet 11. The raw material of the insulating layer 13 may further contain a component containing a heavy rare earth element. For example, the raw material of the insulating layer 13 preferably contains 20% by mass to 40% by mass of CaF2 and 60% by mass to 80% by mass of TbF3, where the total of CaF2 and TbF3 is 100% by mass.

[0051] 3. Uses of laminated magnet 10 The applications of the magnet laminate 10 are not particularly limited. The magnet laminate 10 is suitable as a magnet for a motor. The magnet laminate 10 has low eddy current loss generated inside and can concentrate magnetic flux, so it can contribute to one or more of the following effects: miniaturization of the motor, suppression of heat generation, improvement of heat resistance, and improvement of heat dissipation. In addition, since the insulating layer 13 of the magnet laminate 10 is mainly composed of inorganic crystals, its insulating performance is less likely to change due to the influence of humidity, temperature, and deterioration over time compared to insulating layers such as resin. Therefore, the magnet laminate 10 is useful for various applications where it is desired that the insulating performance is less likely to change.

[0052] An example of a motor 30 including the magnet stack 10 will be described below with reference to FIGS. 9 and 10. The motor 30 includes a stator 31 and a rotor 33 arranged inside the stator 31. The magnet stack 10 is arranged in the rotor 33, and a winding (not shown) is arranged in the stator 31. The motor 30 in FIG. 9 is an inner rotor type in which the magnet is arranged on the inside (rotating shaft side) and the winding is arranged on the outside. The motor is not limited to the inner rotor type. For example, the motor may be an outer rotor type in which the winding is arranged on the inside (rotating shaft side) and the magnet is arranged on the outside.

[0053] The rotor 33 includes a rotating shaft 34, a rotating core 35, and a plurality of laminated magnets 10. The rotating core 35 is formed by laminating electromagnetic steel sheets. A shaft hole 37 is formed at the center of the rotating core 35. The rotating shaft 34 is inserted into the shaft hole 37. A plurality of magnet holes 39 are formed in the rotating core 35 at intervals in the circumferential direction. A laminated magnet 10 is inserted into each magnet hole 39. Each laminated magnet 10 is arranged with the convex side of the convex curved shape facing the rotating shaft 34. The arrangement of each laminated magnet 10 is not limited to the arrangement in FIG. 10. For example, two magnets may be arranged side by side in an arc shape, as in the rotor of sample C shown in the lower part of FIG. 13.

[0054] 4. Functions and Effects of the Present Embodiment The magnet stack 10 of this embodiment is made up of a plurality of magnets 11 and insulating layers 13 stacked together, so that eddy current loss can be reduced. On the other hand, when the magnet 11 having a convex curved shape is used for the magnet stack 10 as in this embodiment, it is difficult to increase the average orientation measured as described above. For example, the high-pressure magnetic field press method is generally said to be an effective method for increasing the orientation of magnets. However, the high-pressure magnetic field press method is limited to the manufacture of coarse block magnets because of restrictions on the dimensions and shapes of the molding die. Therefore, the high-pressure magnetic field press method is not suitable for the manufacture of thin magnets such as those used for magnet stacks. In addition, for example, it has been considered to manufacture a magnet having a convex curved shape by first aligning a rectangular magnet in a parallel direction and then bending the magnet so that it is convex in a second direction. However, bending the magnet reduces the orientation of the magnet, and it is difficult to ensure a sufficient average orientation when the magnet is bent. The inventors of the present application have conducted intensive research to increase the average orientation of the magnet 11, and have developed the novel magnet stack 10 of the present disclosure.

[0055] Since the laminated magnet 10 has an average degree of orientation of 90% or more, it is able to concentrate magnetic flux. Below, a computer-based simulation is used to study the magnetic flux distribution of Sample A, Sample B, and Sample C when the magnets are applied to rotors. Finite element method electromagnetic field analysis software JMAG (made by JSOL Corporation) was used to study the magnetic flux distribution. The upper graphs of Figures 11 to 13 show the relationship between the angle in the range of a central angle of 90° in the rotor and the magnetic flux density. The magnets described below are used for each rotor. The horizontal axis represents the angle (°) with respect to the straight line OX shown in the rotor in the lower graph. The vertical axis represents the magnetic flux density (W / m 2 ) The lower parts of Fig. 11 to Fig. 13 are images of the rotor and the distribution of magnetic flux density (absolute value) by simulation. The arrows on each magnet roughly indicate the orientation direction of the magnet.

[0056] The magnetic properties of Sample A, Sample B, and Sample C are as follows: <Sample A> Magnet shape in first direction: Rectangular Magnet surface area: 96.8mm 2 (Long side dimension 22mm, short side dimension 4.4mm) Magnet orientation: Parallel orientation Average magnet orientation: 97% Arrangement: Two magnets are arranged in a V shape. <Sample B> Shape of magnet as viewed from the first direction: Arc shape (corresponding to a convex curved shape) Magnet surface area: 96.8mm 2 (The radius of curvature of the outer arc is 25.4 mm, the radius of curvature of the inner arc is 21 mm, the outer arc and the inner arc are concentric, and both have a central angle of 54.3°.) Magnet orientation: Parallel orientation Average magnet orientation: 88% Arrangement: Two magnets are arranged in an arc. <Sample C> Shape of magnet as viewed from the first direction: Arc shape (corresponding to a convex curved shape) Magnet surface area: 96.8mm 2 (The radius of curvature of the outer arc is 25.4 mm, the radius of curvature of the inner arc is 21 mm, the outer arc and the inner arc are concentric, and both have a central angle of 54.3°.) Magnet orientation: radial orientation Average magnet orientation: 95% Arrangement: Two magnets are arranged in an arc.

[0057] The maximum magnetic flux density of sample A is 0.5388 W / m 2 The maximum magnetic flux density of sample B was 0.5521 W / m 2 The maximum magnetic flux density of sample C was 0.5729 W / m 2 Each magnetic flux density is rounded off to the fifth decimal place.

[0058] The properties of "magnet shape," "average degree of orientation," and "maximum magnetic flux density" for Sample A, Sample B, and Sample C are summarized in Table 1 below. Each item is evaluated according to the following criteria. Satisfaction of shape requirements: If the magnet shape was a convex curved shape, it was rated as "satisfied", and if it was anything other than a convex curved shape, it was rated as "not satisfied". Satisfaction of orientation requirements: If the average orientation of the magnets measured using the above method was 90% or more, it was rated as "satisfied", and if it was less than 90%, it was rated as "not satisfied". As can be seen from Table 1, compared to sample A (average orientation 97%, V-shaped arrangement) which uses rectangular magnets, sample B (average orientation 88%, arc-shaped arrangement) and sample C (average orientation 95%, arc-shaped arrangement) which use convexly curved magnets have high magnetic flux density despite their low average orientation. Furthermore, when comparing sample B (average orientation 88%, arc-shaped arrangement) and sample C (average orientation 95%, arc-shaped arrangement), both of which use convexly curved magnets, sample C has a higher magnetic flux density than sample B. From these results, it can be seen that in a convexly curved magnet, the higher the average degree of orientation, the more concentrated the magnetic flux density, resulting in a higher magnetic flux density. Therefore, it can be seen that a convexly curved magnet with an average degree of orientation of 90% or more will have a higher magnetic flux density than a magnet with an average degree of orientation of less than 90%. Sample B, which uses a convexly curved magnet, has a higher magnetic flux density than sample A, which uses a rectangular magnet, even though it has an average degree of orientation of 88%, so it can be seen that when a magnet is convexly curved and the average degree of orientation is 90% or more, sufficient magnetic flux density can be achieved.

[0059] [Table 1]

[0060] Furthermore, in magnet laminate 10, eddy current loss is less likely to change because insulating layer 13 is mainly composed of inorganic crystals. The reason for this is presumed to be as follows. Note that the present disclosure is not limited to this presumed reason. Insulating layer 13 containing inorganic crystals as its main component has almost no change in resistance in the range from room temperature (for example, 25° C.) to 150° C., and is therefore presumed to be capable of reducing eddy current loss over a wide temperature range. In addition, since the insulating layer 13, which is mainly composed of inorganic crystals, has a thermal expansion coefficient close to that of the magnet 11, it is considered that the insulating layer 13 is unlikely to be altered by thermal cycles. -5 / K or less. For this reason as well, it is presumed that the durability (heat resistance) of the magnet laminate 10 of this embodiment is improved.

[0061] In the magnet stack 10 of this embodiment, an insulating layer 13 is present between the magnets 11, 11. With this configuration, the insulating layer 13, which is mainly composed of inorganic crystals, can bond (adhere) the magnets 11, 11 with sufficient strength. In addition, since the insulating layer 13 is mainly composed of inorganic crystals, it can be made thinner while ensuring sufficient bonding strength compared to a bonding layer made of resin or the like. Furthermore, if amorphous glass is used for the insulating layer, unlike in this embodiment, there is a concern that the magnet will oxidize and lose its magnetic properties. On the other hand, since the insulating layer 13 of this embodiment is mainly composed of inorganic crystals, the magnetic properties of the magnet 11 can be suitably secured. EXAMPLES

[0062] The present disclosure will now be described more specifically with reference to examples.

[0063] 1. Fabrication of laminated magnets <Example 1-16> (1) SC alloy preparation process The main raw materials of Nd / Pr alloy, alloy containing Co, Al, Cu, Ga, Zr, and metal single body are mixed to produce strip cast alloy (SC alloy) (for example, composition: Nd2Fe 14 B) was prepared under an argon atmosphere. The SC alloy was a plate-shaped powder with the main surface dimensions of 10 mm x 10 mm to 20 mm x 20 mm.

[0064] (2) Hydro-crushing process The SC alloy was allowed to absorb hydrogen in a hydrogen furnace (hydrogen atmosphere, 200°C, 2 hours), embrittling the grain boundaries (neodymium-rich phase) of the SC alloy.

[0065] (3) Coarse grinding process, first lubricant addition process A lubricant was added to the SC alloy powder that had been through the hydrogen crushing process. Methyl caprylate was used as the lubricant. The lubricant was mixed at a ratio of 0.03% to 0.07% by mass relative to the amount of SC alloy. The SC alloy powder was coarsely crushed in a nitrogen or argon atmosphere using a stirrer while the lubricant was added. The average particle size of the SC alloy after coarse crushing was 50μm to 500μm.

[0066] (4) Fine grinding process, second lubricant addition process The SC alloy powder after adding the lubricant was finely pulverized in a nitrogen atmosphere using a jet mill. The average particle size D50 after fine pulverization was 2.0 μm-3.5 μm. A lubricant was added to the finely pulverized SC alloy powder. Methyl laurate was used as the lubricant. The mixing ratio of the lubricant to the amount of the SC alloy was 0.05% to 0.1% by mass.

[0067] (5) Powder filling process, orientation process, molding process The powder of the SC alloy after the fine pulverization step and the second lubricant addition step was filled into each molding space of a mold provided with multiple partition plates in a nitrogen atmosphere. Each compact formed in each molding space corresponds to each magnet to be stacked in a later step. The planar shape of each "magnet 11" was an arc shape with a central angle of 180°, with the curve C1 having a radius of curvature of 15 mm, the opposing line C2 having a radius of curvature of 12 mm, and the curve C1 and the opposing line C2 being concentric. After the powder was packed into the mold, a magnetic field (e.g., 5000 V) was applied in the planar direction of each compact (perpendicular to the thickness direction) to align the orientation of the SC alloy powder. A radial magnetic field (a magnetic field in which magnetic lines of force spread radially) was used. The SC alloy powder packed into the mold was compressed to form an SC alloy compact. The conditions for the compression molding were pressure: 5 MPa-20 MPa, packing density: 3.0 g / cm. 3 -4.0g / cm 3 , relative density: 40%-52%.

[0068] (6) Mold removal process, first firing process The outer frame was removed from the mold, and a continuous alternating pattern of compacts and partition plates (material to be sintered) was prepared. To remove hydrogen, the material to be sintered (with partition plates) was heated in an Ar atmosphere at 500°C for 3-4 hours. After that, the material to be sintered (with partition plates) was held at 930°C-1050°C for 3 hours and sintered in a vacuum atmosphere.

[0069] (7) Insulation layer coating process After the first firing step, the partition plate was removed from the fired object, and the raw material for the insulating layer was applied to six surfaces of the magnet before lamination. The raw material for the insulating layer was a mixture of the main component compound powders listed in Table 2, TbF3 compound powder, and a solvent. The ratio of the TbF3 compound powder in the raw material for the insulating layer was 10% by mass to 20% by mass. The applied thickness of the raw material for the insulating layer was 12 μm or more and 14 μm or less. The raw material for the insulating layer was applied in the air by a spray method.

[0070] (8) Laminate temporary fixing process 25 magnets coated with an insulating layer were stacked in air and temporarily fixed. The number of stacked magnets was adjusted so that the dimension of the stacked magnet in the stacking direction was 50 mm. This method makes it possible to manufacture plate-shaped magnets without the need for a cutting process or other process to cut out plate-shaped magnets from a larger magnet.

[0071] (9) Hot pressing process The temporarily fixed laminate was placed in a hot press mold and subjected to uniaxial hot pressing. The hot pressing conditions for each example were as shown in Table 1. In Table 1, "vac" in "Atmosphere" indicates vacuum and "Ar" indicates argon atmosphere. The hot pressing pressure time was 1 second to 1 hour, and the hot pressing heat treatment time was 10 minutes to 20 hours. As a result, a laminate magnet sample for each example was produced.

[0072] <Comparative Example 1-5> In Comparative Example 1-5, the insulating layer coating step and the pressing step described below were carried out instead of the insulating layer coating step (7) and the hot pressing step (9) described above. The steps other than the insulating layer coating step and the pressing step described below were the same as the steps (1)-(6) and (8) described above for Example 1-16 to produce laminated magnet samples for each Comparative Example.

[0073] In Comparative Example 1-5, in the insulating layer coating process, a mixture of TbF3 compound powder and a solvent was first coated. Next, the surface was heat-treated until the coating film was removed. After that, a resin with the main component shown in Table 1 was coated.

[0074] In the press process of Comparative Examples 1 to 5, the temporarily fixed laminate was placed in a press mold and pressed with uniaxial pressure. The press conditions for each Comparative Example were as shown in Table 2. In Table 2, "air" in "atmosphere" indicates the atmospheric conditions.

[0075] 2. Characteristics of Examples and Comparative Examples Table 2 shows the properties of the magnets and insulating layers of each of the examples and comparative examples. The "Type" column of "Magnet" indicates the type of magnet. "Neodymium magnet" is Nd2Fe 14 This indicates that the magnet has B as the main phase. The column "Average orientation" indicates the average orientation measured by the method described in the embodiment. The "Main Component" column of the "Insulating Layer" indicates the compound with the largest amount (mass%) contained in the insulating layer. The components of the insulating layer were identified by EPMA and XRD, and organic substances were identified by NMR and IR analysis. In both the examples and comparative examples, the content (mass%) of the main component was 65% or more when the entire insulating layer was taken as 100% by mass. The amount (mass%) of inorganic crystals was calculated by determining the presence of inorganic crystals by micro X-ray analysis or XRD analysis and combining it with the composition analysis by EPMA. In the comparative examples, the components other than inorganic crystals in the insulating layer were considered to be the main components, and the content of the main component was calculated by subtracting the amount (mass%) of inorganic crystals from 100 (mass%). The column "Thickness" of "Insulating Layer" indicates the thickness of the insulating layer, which was measured by observing the cross section of the laminated magnet with a SEM (scanning electron microscope). The "Number of divisions" column of "Laminated magnet" indicates the number of layers of the "magnet" as described above.

[0076] [Table 2]

[0077] 3.Performance evaluation (1) Eddy current loss (25℃, 1kHz) evaluation method The eddy current loss of the examples and comparative examples was measured at 25° C. and 1 kHz. Specifically, each sample of the examples and comparative examples was sandwiched between the magnetic poles of a C-type core, and the loss at a frequency of 1 kHz and a magnetic flux density of 0.01 T was measured with a wattmeter.

[0078] The evaluation was as follows: Eddy current loss (25℃, 1kHz) “A”…90W / kg or less "B": greater than 90W / kg and less than 105W / kg "C": greater than 105W / kg

[0079] (2) Thermal cycle test The following heat cycle test was conducted to evaluate the heat resistance of the examples and comparative examples. The heat cycle consisted of a low temperature of 25°C and a high temperature of 180°C (1 minute) per cycle, and the number of heat cycles was 1000. The bending strength (MPa) of each sample after the test was measured in accordance with JIS R1664:2004. The bending strength (MPa) of the sample before the test was set as 100%, and the reduction rate (%) of the bending strength of the sample after the test was calculated. A low reduction rate (%) of the bending strength of the sample after the test is an indicator of high durability (heat resistance).

[0080] The evaluation was as follows: "A": Bending strength reduction rate of 5% or less "B": Decrease in bending strength is greater than 5% and less than 12% "C": Decrease in bending strength is greater than 12%

[0081] (3) Eddy current loss (150℃, 1kHz) evaluation method The eddy current loss of the examples and comparative examples was measured at 150°C and 1 kHz under the same conditions as the above eddy current loss (25°C, 1 kHz) except for the temperature. The eddy current loss at 25°C and 1 kHz was set as 100%, and the rate of change (%) of the eddy current loss at 150°C and 1 kHz was calculated.

[0082] The evaluation was as follows: "A": Eddy current loss change rate 5% or less "B": Eddy current loss change rate is greater than 5% and less than 10% "C": Eddy current loss change rate is greater than 10%

[0083] 4. Evaluation Results The evaluation results are shown in Table 2. Examples 1 to 16 satisfy the following requirements (a) to (d). In contrast, Comparative Examples 1 and 3 to 4 do not satisfy requirement (d). Comparative Example 2 does not satisfy requirements (c) and (d). Requirement (a): The magnet is a laminated magnet in which a plurality of magnets and insulating layers are laminated in a first direction. Requirement (b): The magnet contains a rare earth element and has a curved shape that is convex in a second direction when viewed from a first direction. Requirement (c): When viewed from the first direction, the average orientation of each portion of a 1 mm width centered on the normal line at multiple points from one end to the other end on the curve on the convex side in the second direction on the outer periphery of the magnet is 90% or more. Requirement (d): The insulating layer is composed mainly of inorganic crystals.

[0084] In Example 1-16, the eddy current loss at 25° C. and 1 kHz was evaluated as either "A" or "B," and the eddy current loss at 150° C. and 1 kHz was evaluated as either "A" or "B." It was suggested that Example 1-16 could reduce eddy current loss.

[0085] Among Examples 1-16, Example 1-3, which further satisfied the following requirement (e), received an "A" in the evaluation of eddy current loss at 25° C. and 1 kHz, the evaluation of thermal cycle test, and the evaluation of eddy current loss at 150° C. and 1 kHz. This suggests that by satisfying requirement (e), eddy current loss can be further reduced and eddy current loss is less likely to change. Requirement (e): The inorganic crystal contains a fluoride from Group 2A of the periodic table.

[0086] 5. Effects of the embodiment In this embodiment, the eddy current loss generated inside could be reduced. Also, in the present embodiment, Example 1-16, the average degree of orientation is 90% or more, so that the magnetic flux can be concentrated.

[0087] The present invention is not limited to the above-described embodiments, and various modifications and variations are possible within the scope of the claims of the present invention. [Explanation of symbols]

[0088] 10...Laminated magnet 11...Magnet 13...Insulating layer 30…Motor 31…Stator 33…Rotor 34…Rotation axis 35...Rotating core 37…Shaft hole 39…Magnetic hole

Claims

[Claim 1] A laminated magnet in which a plurality of magnets and insulating layers are laminated in a first direction, the magnet contains a rare earth element and has a curved shape that is convex in a second direction when viewed from the first direction, The average orientation degree of each portion of a 1 mm width centered on a normal line at a plurality of points from one end to the other end on the outer periphery of the magnet as viewed from the first direction is 90% or more, The insulating layer is a laminated magnet mainly composed of inorganic crystals.

Citation Information

Patent Citations

  • Permanent magnet and motor

    JP2003164083A

  • R-t-b-c rare earth sintered magnet

    JP2007157903A

  • Rare earth permanent magnet, manufacturing method for rare earth permanent magnet, and motor

    JP2013219911A

  • Rare-earth magnet and motor

    JP2017174962A

Cited By

  • Magnetic field line generator

    JP7852127B1